Solution Phase and Nanoparticular Biosynthetically Inspired Interconnections in the Canthin‐6‐one β‐Carboline Series and Study of Phenotypic Properties on C. elegans (Eur. J. Org. Chem. 26/2013). Issue 26 (4th September 2013) - Cebrián‐Torrejón, Gerardo; Mackiewicz, Nicolas; Vázquez‐Manrique, Rafael P.; Fournet, Alain; Figadère, Bruno; Nicolas, Julien; Poupon, Erwan
Abstract : The cover picture shows an intricate combination of elements tracing the different aspects of the paper by E. Poupon et al. Leaves and fruits of Zanthoxylum chiloperone var. angustifolium, a tree growing in Paraguay from which the alkaloid canthin‐6‐one is extracted, appear in the background along with microscopic views of nanoparticles. In this paper, the biosynthetic pathway of this small β‐carboline alkaloid has been mimicked in the lab through chemical synthesis including mimicry of a crucial step from a precursor covalently grafted onto a nanoparticle‐forming polymer. Crossing the cover picture, specimens of Caenorhabditis elegans illustrate part of the work dedicated to a better understanding of the role of canthin‐6‐one in terms of chemical ecology. Details of this work are described in the Full Paper by E. Poupon et al. onpage 5821 ff.